Root morphology can be a risk factor for periodontal damage and root resorption in orthodontic movement - Zaniboni, Ewerton; Filho, Mário Vedovello; Santamaria, Mauro Pedrine [UNESP]; Jardini, Maria Aparecida Neves [UNESP]; Martins-Ortiz, Maria Fernanda; Consolaro, Alberto; Junior, Milton Santamaria (Universidade Estadual de Campinas, 2017)
Aim: The study evaluated, using histomorphometry, the percentage of hyaline area in periodontal ligament (PDL) and root resorption in orthodontic tooth movement (OTM). Methods: Ten rats were divided into two groups. G3 Group (n=5), with 3 days of OTM and G7 Group (n=5), with 7 days of OTM. A Control Group (n=5) consisted of contralateral teeth of each animal, which were not moved. Maxillary left first molar was moved, using stainless steel spring connected to the incisors with 40g force. Microscopic analysis was done in transversal sections of the mesiovestibular (MV) and distovestibular (DV) roots in the cervical level. Results: There was a PDL hyaline area in the DV root of 6.2% in G3 and 1.8% in G7. The root resorption area in G7 was 0.9%. On MV root and Control Group were not found occurrences of hyaline areas in PDL and no root resorption. Conclusions: Based on the results obtained, it might be concluded that smaller roots showed higher frequency of hyaline areas and root resorption.
Keywords: Orthodontics; Periodontal ligament; Root resorption; Tooth movement